ANALISIS INVOICE FINANCING PADA FINTECH SYARIAH (PT. Alami Fintek Sharia) - Salekhah, Fitri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
Alami one of the fintech organizer platforms is registered and licensed at the OJK on May 27, 2020 under the company name PT Alami Fintek Syariah which has a Sharia based business type. Invoice financing in Alami is financing in the form of bill management services based on invoice evidence, either with or without a bailout (qard) given to business actors who have invoice to third parties (payor). The performance platform is inseparable from the company’s strategy that optimizes sector sector collaboration, industry and business projections, and retail optimization. The success of the Alami platform’s performance proves that Alami has won the trust of customers both from funders and also from recipients with a total of 272 existing lists of financing. Product of Alami according to the Fatwa DSN-MUI No. 117/ DSN_MUI/ II/ 2018, because the legal subject has met the requirements, namely there is an organizer (Alami), a recipient of financing (in this case 272 total financing lists) and providers of financing using al qordh and wakalah bil ujrah contracts who have entered into the DSN_MUI fatwa.